Cause or compensation? Complex changes in cerebello-thalamo-cortical networks in pathological action tremor. (16th September 2015) - Raethjen, Jan; Muthuraman, Muthuraman
Abstract : This scientific commentary refers to 'Intrinsic signature of essential tremor in the cerebello-frontal network' by Gallea et al . (doi:10.1093/brain/awv171 ).